Effects of chili straw on rumen fermentation, meat quality, amino acid and fatty acid contents, and rumen bacteria diversity in sheep - Jinlong Li; Jinlong Li; Jinlong Li; Yong Tuo; Yong Tuo; Yong Tuo; Linjiao He; Linjiao He; Linjiao He; Yan Ma; Yan Ma; Zhijun Zhang; et al. (Frontiers in Microbiology)
Crop residues have shown promise as non-conventional feed sources to enhance animal health and growth. This study evaluated the effects of chili straw (CS) on rumen fermentation, meat quality, amino and fatty acid composition, and rumen microbial diversity in sheep. Fifty F1 Dorper×Hu lambs (29.58 ± 2.06 kg) were randomly assigned to five groups, fed pelleted feed with 0%, 5%, 10%, 15%, or 20% CS over a 63-day period, including a 7-day pre-test. Post-trial, rumen fluid was sampled to assess fermentation and microbial profiles, and slaughter performance and meat quality were evaluated. Key findings include: (1) No significant differences were observed in rumen pH, NH3-N, or acetic acid-to-propionic acid ratio across groups (P > 0.05). (2) Rumen microbial diversity indices did not vary significantly between groups (P > 0.05), though the relative abundance of Firmicutes and Proteobacteria increased, and Bacteroidota decreased in CS-fed groups, with specific genus-level changes. (3) Carcass weight decreased in the CS20% group (P < 0.01). (4) Cooking loss decreased in CS10%, 15%, and 20% groups (P < 0.05), and meat redness increased in CS15% and 20% groups (P < 0.01). (5) Saturated fatty acids decreased, while the PUFA/SFA ratio and amino acid profiles, including sulfur-containing amino acids (SAA), dibasic amino acids (DAA), essential amino acids (EAA), and total amino acids (TAA), increased with CS, with a significant rise in Gly content in the CS15% group (P < 0.05). In conclusion, incorporating CS into lamb diets can enhance meat quality without adversely affecting rumen fermentation, with recommended levels between 10% and 15%.